Plant responses to decadal scale increments in atmospheric CO2 concentration: comparing two stomatal conductance sampling methods - Yiotis, Charilaos; Mc Elwain, Jennifer (Springer Science and Business Media LLC, 2020)
Our study demonstrated that the species respond non-linearly to increases in CO2 concentration when exposed to decadal changes in CO2, representing the year 1987, 2025, 2051, and 2070, respectively. There are several lines of evidence suggesting that the vast majority of C3 plants respond to elevated atmospheric CO2 by decreasing their stomatal conductance (gs). However, in the majority of CO2 enrichment studies, the response to elevated CO2 are tested between plants grown under ambient (380-420 ppm) and high (538-680 ppm) CO2 concentrations and measured usually at single time points in a diurnal cycle. We investigated gs responses to simulated decadal increments in CO2 predicted over the next 4 decades and tested how measurements of gs may differ when two alternative sampling methods are employed (infrared gas analyzer [IRGA] vs. leaf porometer). We exposed Populus tremula, Popolus tremuloides and Sambucus racemosa to four different CO2 concentrations over 126 days in experimental growth chambers at 350, 420, 490 and 560 ppm CO2; representing the years 1987, 2025, 2051, and 2070, respectively (RCP4.5 scenario). Our study demonstrated that the species respond non-linearly to increases in CO2 concentration when exposed to decadal changes in CO2. Under natural conditions, maximum operational gs is often reached in the late morning to early afternoon, with a mid-day depression around noon. However, we showed that the daily maximum gs can, in some species, shift later into the day when plants are exposed to only small increases (70 ppm) in CO2. A non-linear decreases in gs and a shifting diurnal stomatal behavior under elevated CO2, could affect the long-term daily water and carbon budget of many plants in the future, and therefore alter soil-plant-atmospheric processes.
PUBLISHED
Keywords: Growth chambers; Climate change; IRGA; Porometer; Water loss